Glycerol monolaurate and dodecylglycerol effects on Staphylococcus aureus and toxic shock syndrome toxin-1 in vitro and in vivo. - Ying-Chi Lin; Patrick M Schlievert; Michele J Anderson; Christina L Fair; Matthew M Schaefers; Ramaiah Muthyala; Marnie L Peterson (PLoS ONE)
Background Glycerol monolaurate (GML), a 12 carbon fatty acid monoester, inhibits Staphylococcus aureus growth and exotoxin production, but is degraded by S. aureus lipase. Therefore, dodecylglycerol (DDG), a 12 carbon fatty acid monoether, was compared in vitro and in vivo to GML for its effects on S. aureus growth, exotoxin production, and stability. Methodology/principal findings Antimicrobial effects of GML and DDG (0 to 500 microg/ml) on 54 clinical isolates of S. aureus, including pulsed-field gel electrophoresis (PFGE) types USA200, USA300, and USA400, were determined in vitro. A rabbit Wiffle ball infection model assessed GML and DDG (1 mg/ml instilled into the Wiffle ball every other day) effects on S. aureus (MN8) growth (inoculum 3x10(8) CFU/ml), toxic shock syndrome toxin-1 (TSST-1) production, tumor necrosis factor-alpha (TNF-alpha) concentrations and mortality over 7 days. DDG (50 and 100 microg/ml) inhibited S. aureus growth in vitro more effectively than GML (p<0.01) and was stable to lipase degradation. Unlike GML, DDG inhibition of TSST-1 was dependent on S. aureus growth. GML-treated (4 of 5; 80%) and DDG-treated rabbits (2 of 5; 40%) survived after 7 days. Control rabbits (5 of 5; 100%) succumbed by day 4. GML suppressed TNF-alpha at the infection site on day 7; however, DDG did not (<10 ng/ml versus 80 ng/ml, respectively). Conclusions/significance These data suggest that DDG was stable to S. aureus lipase and inhibited S. aureus growth at lower concentrations than GML in vitro. However, in vivo GML was more effective than DDG by reducing mortality, and suppressing TNF-alpha, S. aureus growth and exotoxin production, which may reduce toxic shock syndrome. GML is proposed as a more effective anti-staphylococcal topical anti-infective candidate than DDG, despite its potential degradation by S. aureus lipase.